The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1996
DOI: 10.1093/infdis/173.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma Levels of Tumor Necrosis Factor (TNF)-α, Soluble TNF Receptors, Interleukin (IL)-6, and IL-IO in Patients with Hemorrhagic Fever with Renal Syndrome

Abstract: Plasma levels of cytokines were measured by EIA in 15 subjects hospitalized with nephropathia epidemica, a European form of hantavirus-induced hemorrhagic fever with renal syndrome. Concentrations of tumor necrosis factor (TNF)-alpha and interleukin (IL)-6 were increased in all patients at admission, and the concentration of IL-10 was increased in most. TNF-alpha concentrations were still increased 1 week after onset of disease; levels of IL-6 and IL-10 were normalized. TNF-alpha was undetectable by the WEHI c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
130
1
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(142 citation statements)
references
References 25 publications
8
130
1
3
Order By: Relevance
“…Similar elevations of these cytokines are seen following infection with other lentiviruses (Maury & Lahdevirta, 1990 ;Allen et al, 1991 ;Lehmann et al, 1992), as well as non-retroviruses (Torre et al, 1994 ;Linderholm et al, 1996) Systemic levels of TNF-α clearly increase during clinical EIA. The elevated TNF-α levels found in bone marrow from Pre-Tp foals may reflect this increased systemic activity, or it may represent increased activity produced within the local bone marrow environment.…”
Section: Discussionmentioning
confidence: 80%
“…Similar elevations of these cytokines are seen following infection with other lentiviruses (Maury & Lahdevirta, 1990 ;Allen et al, 1991 ;Lehmann et al, 1992), as well as non-retroviruses (Torre et al, 1994 ;Linderholm et al, 1996) Systemic levels of TNF-α clearly increase during clinical EIA. The elevated TNF-α levels found in bone marrow from Pre-Tp foals may reflect this increased systemic activity, or it may represent increased activity produced within the local bone marrow environment.…”
Section: Discussionmentioning
confidence: 80%
“…This is in agreement with the results of Kim et al [25] . It has been reported that increased plasma levels of TNF-α were found in the blood of HFRS patients during the acute phase [28] . The results of Niikura et al [29] confirmed that HTNV infection of endothelial cells might contribute to increased vascular leakage through a prolonged response to TNF-α.…”
Section: Arbidol Is Effective Against Htnv In Vivomentioning
confidence: 96%
“…[11][12][13][14] On the other hand, it has been shown that TNF-␣ decreases the accumulation of viral nucleoproteins in Vero E6 cells infected with Sin Nombre virus. 15 Accordingly, hantavirus nucleocapsid proteins antagonize the signaling pathway of TNF-␣, suggesting that this cytokine may play a role in the immune response against hantavirus.…”
Section: Discussionmentioning
confidence: 99%